Decellularized xenogenic meniscus as a replacement for meniscal tissue - Körber, Ludwig; Mauer, Julia; Rösch, Rebecca; Tluczynski, Katharina; Schwarz, Silke; Rotter, Nicole; Buchholz, Rainer; Breiter, Roman (European Cells and Materials, Vol. 31, Suppl. 1, 2016)

Nintedanib reduces alloimmune-induced chronic airway changes in murine tracheal allografts - Mauer, Julia; Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Ensminger, Stephan M.; Distler, Jörg; Weyand, Michael; Heim, Christian (Transplant Immunology, 2022)
Background: The major obstacle for long-term survival after successful lung transplantation is the development of bronchiolitis obliterans (BO) which is one phenotype of chronic lung allograft dysfunction (CLAD). Nintedanib has beneficial effects treating neoplastic diseases and idiopathic pulmonary fibrosis by blocking tyrosine kinase receptors. These receptors play an important role in alloimmune-mediated proliferative diseases. The aim of this study was to determine the effect of nintedanib on proliferative airway changes after orthotopic trachea transplantation in mice. Methods: C57BL/6 mice (H-2b) donor tracheas were orthotopically transplanted into CBA/J mice (H-2k). After transplantation, recipients were daily treated with nintedanib (60 mg/kg; p.o.). Histological and immunofluorescence analysis were performed after 30 days and intragraft gene expression measurements after 14 days of treatment, respectively. Results: Tracheal allografts from mice treated with nintedanib showed significantly less features of chronic rejection than untreated allografts reflected in a higher epithelium/lamina propria ratio (ELR) [ELR: 0.65 ± 0.13 nintedanib vs. 0.50 ± 0.07 untreated controls; p < 0.05] and a reduced submucosal smooth muscle actin (SMA) content [SMA: 1.26% ± 0.78% nintedanib vs. 2.18% ± 1.01% untreated controls; p < 0.01]. Furthermore, lower T cell, macrophage and dendritic cell infiltration was detected in the nintedanib treated grafts. The protein and intragraft mRNA expression of receptor subtypes was considerably decreased in grafts of nintedanib treated mice. The mRNA expression of relevant immune mediators was affected by nintedanib treatment. Conclusion: Receptor blocking by nintedanib reduced alloimmune-induced inflammation and chronic airway changes in mouse trachea allografts and might be a promising approach to diminish the development of BO in lung transplants.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Bronchiolitis obliterans; Chronic rejection; Nintedanib; Tracheal allografts; Tyrosine kinase inhibitor